MCP-1-CCR2-M2 macrophages axis contributes to diffuse large B-cell lymphoma progression and inhibits antitumor immune response - Zhao-Feng Wen; Qi-Tang Huang; Yang-Yang Wang; Feng-Ya Nan; Zhi-Min Zhai; Yan-Li Li (Scientific Reports)
Abstract Diffuse large B-cell lymphoma (DLBCL) is an aggressive hematological malignancy with restricted effective therapy choices. Neither the recruitment of monocytes nor the functioning of the physiological mechanisms of macrophage polarization can be achieved without the involvement of the MCP-1/CCR2 axis. We investigated the feasibility of treatment targeting MCP-1-CCR2-macrophages axis in DLBCL. MCP-1, CD68, CD163 expression was analyzed by immunohistochemistry in 143 DLBCL patients tissues, and MCP-1 concentration and CD14 + CCR2 + monocytes in peripheral blood were analyzed in another cohort by enzyme linked immunosorbent assay or flow cytometry. THP-1 or U937 cells were used to mimic macrophages polarization with or without the blockade of MCP-1/CCR2 axis in vitro. BALB/C mice subcutaneous tumors were evaluated and detected after blocking MCP-1/CCR2 axis with CCR2 antagonist. MCP-1, CD68, CD163 expression and proportion of CD14 + CCR2 + monocytes in peripheral blood are prognostic for DLBCL patients. MCP-1 expression is positively associated with CD68 or CD163 expression in DLBCL. CCR2 antagonist intervention produces a blocking effect on the MCP-1/CCR2 signaling axis. This not only significantly inhibits monocyte recruitment in vitro and hinders the polarization of M2 macrophages toward a pro-tumorigenic phenotype, but also stimulates CD8 + T cell expansion. Under the synergistic effect of multiple mechanisms, the growth process of subcutaneous tumor was effectively suppressed. MCP-1-CCR2-M2 macrophages polarization plays vital roles in DLBCL progression. The results demonstrate the translational potential of MCP-1/CCR2 blockade for treatment of DLBCL.